EXPLORING STUDENT FEEDBACK ON A CUSTOM-BUILT MOBILE QUIZ APP FOR THE REPRODUCTIVE PHYSIOLOGY MODULE - Nasibah Azme, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The use of mobile quiz application in the field of medical education is rising because it offers new approaches for increasing the level of learner’s participation and performance. This study aims to explore student’s feedback on the development and effectiveness of the Reproductive Physiology Quiz app, a custom-built mobile application for quizzes that enhances learning in the Reproductive Physiology module. The app is developed using Buildbox and contains features like the life system (nyawa), which is based on mastery learning and immediate feedback on incorrect answers. About ten Year 2 medical students had recently completed the Reproductive Physiology module involved in the pilot study of this custom-built mobile app. Their feedbacks were acquired through a questionnaire that contained both multiple-choice-close-ended and open-ended questions. The study revealed that 100% of the students reported that the app was appealing and enhanced their learning experience, while 90% stated that it was helpful in evaluating their knowledge. The qualitative data revealed some suggestions for improvement such as the need for different types of questions, random order of questions, and the need for more elaboration of the answers. The open-ended responses also pointed out the possible directions for improvement, such as the different types of questions, the different order of the questions, and the more detailed explanations of the answers. Furthermore, the learners also agreed that the app offers flexibility for self-assessment and recalls their knowledge on reproduction. These results indicate that mobile quiz applications such as Repro Quiz may increase student engagement, knowledge, and self-learning in medical education. Future studies should aim at extending the app to include other modules and incorporating the feedback of a larger cohort of students to enhance the features and usability of the app.